Overexpressed NaV1.7 Channels Confer Hyperexcitability to in vitro Trigeminal Sensory Neurons of CaV2.1 Mutant Hemiplegic Migraine Mice - Mehboob, Riffat; Marchenkova, Anna; van den Maagdenberg, Arn M. J. M.; Nistri, Andrea (Frontiers in Cellular Neuroscience, 2021)
Trigeminal sensory neurons of transgenic knock-in (KI) mice expressing the R192Q missense mutation in the α 1A subunit of neuronal voltage-gated CaV2.1 Ca2+ channels, which leads to familial hemiplegic migraine type 1 (FHM1) in patients, exhibit a hyperexcitability phenotype. Here, we show that the expression of NaV1.7 channels, linked to pain states, is upregulated in KI primary cultures of trigeminal ganglia (TG), as shown by increased expression of its α1 subunit. In the majority of TG neurons, NaV1.7 channels is co-expressed with ATP-gated P2X3 receptors (P2X3R), which are important nociceptive sensors. Reversing the trigeminal phenotype with selective CaV2.1 channel inhibitor ω-agatoxin IVA inhibited NaV1.7 overexpression. Functionally, KI neurons revealed a TTX-sensitive inward current of larger amplitude that was partially inhibited by selective NaV1.7 blocker Tp1a. Under current-clamp condition, Tp1a raised the spike threshold of both wild-type (WT) and KI neurons with decreased firing rate in KI cells. NaV1.7 activator OD1 accelerated firing in WT and KI neurons, a phenomenon blocked by Tp1a. Enhanced expression and function of NaV1.7 channels in KI TG neurons result in higher excitability and facilitated nociceptive signaling. Co-expression of NaV1.7 channels and P2X3Rs in TGs may explain how hypersensitivity to local stimuli can be relevant to migraine.